2010
DOI: 10.2196/jmir.1438
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Web-based Interventions for Heart Disease Self-Management: A Mixed Methods Investigation

Abstract: BackgroundExisting initiatives to support patient self-management of heart disease do not appear to be reaching patients most in need. Providing self-management programs over the Internet (web-based interventions) might help reduce health disparities by reaching a greater number of patients. However, it is unclear whether they can achieve this goal and whether their effectiveness might be limited by the digital divide.ObjectiveTo explore the effectiveness of a web-based intervention in decreasing inequalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…In two studies, satisfaction with OHITs was equal to that of face-to-face interventions (Nguyen et al, 2008(Nguyen et al, , 2013. Older patients who were more experienced with using the Internet were more likely to become either moderate or heavy OHIT users (Kerr et al, 2010). Because of technological issues, one study found OHIT usage to be sub-optimal (Nguyen et al, 2008).…”
Section: Immediate Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies, satisfaction with OHITs was equal to that of face-to-face interventions (Nguyen et al, 2008(Nguyen et al, , 2013. Older patients who were more experienced with using the Internet were more likely to become either moderate or heavy OHIT users (Kerr et al, 2010). Because of technological issues, one study found OHIT usage to be sub-optimal (Nguyen et al, 2008).…”
Section: Immediate Outcomesmentioning
confidence: 99%
“…Ten articles reported on a sample or subsample with a mean age between 65 and 70 years (Bond et al, 2007(Bond et al, , 2010Kerr et al, 2010;Mewton et al, 2013;Neafsey et al, 2011;Nguyen et al, 2008Nguyen et al, , 2013Ruland et al, 2013;Westlake et al, 2007;Zou et al, 2012), 14 articles used a sample or subsample with a mean age between 70 and 75 years (Berman et al, 2013;Hill-Kayser et al, 2011;Homenko et al, 2010;McKinstry et al, 2013;Nahm et al, 2008;Shea et al, 2006Shea et al, , 2009Sheeran et al, 2011;Trief et al, 2007Trief et al, , 2009Trief et al, , 2013Weinstock et al, 2011), and one article used a sample with a mean age of 79 years (Finkelstein et al, 2011). Four articles discussed OHITs based on a single function: three of which were concerned with information provision Sheeran et al, 2011) …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of accrual to this study was low, although larger health care and epidemiological studies that used the Internet to recruit participants have reported enrollment rates of 0.2%-16.9% (Glasgow et al, 2010;Koo & Skinner, 2005;Stopponi et al, 2009). The ICPI study click-through rate was slightly higher than that of other health care advertisements online (Webtrends, 2011); however, the cost per recruited subject as a result of this advertising was significantly higher than other research that recruited in the same manner, reporting their cost at $5.14 per participant (Bull, Vallejos, Levine, & Ortiz, 2008).…”
Section: Discussion Feasibilitymentioning
confidence: 78%
“…The ICPI was well received by participants and demonstrated positive outcomes in this preliminary study. Further research with more participants is feasible and While research has established the effectiveness of these therapies, delivered via traditional face-toface methods, for those with chronic pain (Broderick et al, 2014;Hoffman, Papas, Chatkoff, & Kerns, 2007;LeFort, Gray-Donald, Rowat, & Jeans, 1998;McCracken, MacKichan, & Eccleston, 2007;Nicholas et al, 2010;Reid et al, 2008;Sveinsdottir, Eriksen, & Reme, 2012), early studies documenting delivery of these therapies online involved individuals with depression, anxiety, other social and mood disorders (Andersson, 2006;Andersson, Bergstrom, Carlbring, & Lindefors, 2005;, and other chronic diseases (Ghahari, Packer, & Passmore, 2009;Kerr et al, 2010;Lorig, Ritter, Laurent, & Plant, 2006). The effect of an Internet-based chronic pain psycho-educational intervention that included selfmanagement and CBT had not been studied in depth prior to initiation of this project.…”
mentioning
confidence: 99%